2012
DOI: 10.4103/2006-8808.110271
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Epidural Haematoma in Sickle Cell Anaemia: Case Report and Literature Review

Abstract: Non traumatic spontaneous epidural Haematoma is a rare and often unmentioned complication of sickle cell disease. It is often associated with skull bone infarction. We report an eighteen year old boy with sickle cell anaemia who developed persistence headache during a vaso-occlusive crisis. Brain computed tomography (CT) revealed a right frontal epidural Haematoma (EDH) compressing on the brain. No other etiologic factor was identified. A right frontal craniotomy and evacuation of the Haematoma was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Three pathophysiologic explanations have been proposed over the years for the causation of this rare entity: (1) Vaso-occlusion of the haematopoietically active calvarial diploic bone resulting in bone infarction and subsequent leaking of blood and proteinaceous material in the subperiosteal, epidural, or subgaleal space [3841, 43, 45]. (2) Acute rapid expansion of hematopoiesis with resultant microfracture of already thinned inner cortex and extravasation of blood and hematopoietic tissue [24, 28, 36]. (3) Sludging of sickle cells in the diploic veins hampering venous drainage and oozing of blood due to vascular injury and elevated back pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Three pathophysiologic explanations have been proposed over the years for the causation of this rare entity: (1) Vaso-occlusion of the haematopoietically active calvarial diploic bone resulting in bone infarction and subsequent leaking of blood and proteinaceous material in the subperiosteal, epidural, or subgaleal space [3841, 43, 45]. (2) Acute rapid expansion of hematopoiesis with resultant microfracture of already thinned inner cortex and extravasation of blood and hematopoietic tissue [24, 28, 36]. (3) Sludging of sickle cells in the diploic veins hampering venous drainage and oozing of blood due to vascular injury and elevated back pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that coagulopathies may be responsible for spontaneous bleeding, including epidural bleeding. 41 In the present study, the observed coagulopathies (►Table 3) were: sickle cell anemia (SCA), 2,42,43,44,45,46,47,48,49,50 coagulation factor XIII deficiency, 51,52 hypofibrinogenemia, 53,54 vitamin K deficiency, 55 congenital afibrinogenemia, 56,57 immune thrombocytopenic purpura, 27,58 myelodysplastic syndrome, 59 disseminated intravascular coagulation (DIC), 60 and liver disease 61 . Coagulation disorders and pericranial infections are the two major categories of pathologies with which EDH is associated.…”
Section: Coagulopathiesmentioning
confidence: 57%
“…64 Bone infarction has been related to hematoma cases, possibly due to periosteal elevation and disruption of the bone margin. 2 Bone infarction has been reported in long bones, the spine, the sternum, and the ribs and is commonly associated with adjacent edema and hemorrhage. 66 A literature review conducted in 2015 noted an anatomical correlation between bone infarction and EDH location, but the direct cause has not yet been established.…”
Section: Coagulopathiesmentioning
confidence: 99%
“…[10] Neurosurgical disorders reported in sickle cell patients in the literature include but are not limited to spontaneous epidural hematoma, anaplastic ependymoma, salmonella epidural abscess, moyamoya disease, salmonella enteritis brain abscess, intracranial aneurysms, and vertebral osteomyelitis with epidural abscess. [47815172226] Our study covered a broad spectrum of neurosurgical disorders ranging from trauma, neoplastic, vascular to cosmetic. The high female preponderance in our study is likely attributable to the more prolonged survival of females with sickle cell disease compared to males.…”
Section: Discussionmentioning
confidence: 99%